Analisis Tindak Tutur Dalam Youtube Podcast Warung Kopi (PWK) Episode Brandon Salim Dalam Meningkatkan Kemampuan Keterampilan Menyimak Siswa - Lula Mulyani; Diena San Fauziya (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
This research aims to analyze speech acts in the YouTube Podcast Warung Kopi (PWK) episode of Brandon Salim which was released on October 29 2023, in order to improve students' listening skills. This research uses a qualitative descriptive method that describes symptoms, facts, or events, systematically and accurately. Qualitative descriptive is a method that utilizes qualitative data and explains it descriptively. The results of the analysis show that there are 24 types of speech acts in the podcast, including locutionary, illocutionary, assessive, directive, expressive, commissive, declaration, and perlocutionary. Accessive speech acts are the most dominant with 12 utterances, followed by illocutionary acts with 11 utterances. The use of various types of speech acts reflects the diversity and complexity of communication in the podcast. This analysis reveals that understanding and practicing various speech acts can help students listen more carefully and critically,